大村はまの年間カリキュラムに位置づく入門期古典学習指導 - 坂東 智子; BANDO Tomoko (国語科教育, 2011)
The aim of this paper is to restore the original status of the course of study of the classics for beginners by Hama Ohmura in one year Japanese curriculum, based on the guidance notes by Hama Ohmura and study notes by the learners. Additionally, this paper positively examines the course of study for beginners, designed to resolve-following this curriculum junior high school students' distaste for classical literature. In the unit "Children in the classics," conducted between November and December of 1979, teaching materials were chosen on the yearly theme of Japanese learning, which was "The Lives of Children." Learning methods such as recitation, discussion, and presentation had been repeatedly conducted since April of that year. This report makes clear the concrete relationship between some original plans in each unit of the classics and other studies of Japanese. It also elucidates the conditions of yearly curriculum to lead a successful early stage study course of classical literature. The purpose is to help junior high school students overcome their dislike of the classics.